Some issues of legal regulation of public participation in the environmental matters (Journal of actual problems of jurisprudence, 2019)
Access to information, public participation in decision making and access to justice guaranteed by the Constitutionof the Republic of Kazakhstan . In this article, the authors analyzed the legislation of the Republic of Kazakhstan andthe ways to implement the Aarhus Convention. Existing legislation of the Republic of Kazakhstan gives the publicthe right to obtain information , including environmental information , public access to decision-making and justice.Although the legislation of the Republic of Kazakhstan has legislative strengthening , but is necessary to developspecific procedures and mechanisms for their implementation , taking into account the provisions of the Convention.Key words: Aarhus Convention, the law, the right of access to environmental information, public, environmentalprotection, public access to decision-making and justice.